Controlled supramolecular polymerization of π-systems. Issue 50 (28th May 2020) - Ghosh, Goutam; Dey, Pradip; Ghosh, Suhrit
Abstract : Externally-initiated controlled supramolecular polymerization of the kinetically trapped aggregated state in a chain growth mechanism can produce well-defined living supramolecular polymers and copolymers. Abstract : Supramolecular polymers, albeit having precise internal order, largely lack precision in the mesoscopic scale because in most examples supramolecular polymerization occurs under thermodynamic control through spontaneous self-assembly. Recent reports have exemplified that by varying experimental parameters including cooling rate, solvent composition, interplay of intra- vs. inter-molecular H-bonding and others, it is possible to retard the spontaneous nucleation, and isolate a dormant kinetically controlled monomeric/aggregated state which in turn can serve as the monomer pool to undergo controlled supramolecular polymerization (CSP) through a chain-growth mechanism in the presence of an aggregated/molecular initiator (seed) or by an external stimuli like light. Supramolecular polymers with narrow dispersity, predictable length or stereo-selectivity have been achieved by CSP. Chain extension (similar to "living" polymerization) in such seed initiated CSP is now possible by batch wise addition of monomers, allowing synthesis of supramolecular block copolymers. This feature article describes recent developments in CSP (primarily under kinetic control) of various π-conjugated building blocks.